2015
DOI: 10.1111/tpj.12851
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the celiac disease α‐gliadin complex in wheat: a 33‐mer peptide with six overlapping epitopes, evolved following polyploidization

Abstract: SUMMARYThe gluten proteins from wheat, barley and rye are responsible both for celiac disease (CD) and for nonceliac gluten sensitivity, two pathologies affecting up to 6-8% of the human population worldwide. The wheat a-gliadin proteins contain three major CD immunogenic peptides: p31-43, which induces the innate immune response; the 33-mer, formed by six overlapping copies of three highly stimulatory epitopes; and an additional DQ2.5-glia-a3 epitope which partially overlaps with the 33-mer. Next-generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 41 publications
9
86
0
1
Order By: Relevance
“…Among these, 446 showed a full open reading frame (full ORF). The 18 remaining sequences (3.9 %) had at least one premature stop codon (PSC) and were designated as pseudogenes, in line with previous publications (Noma et al 2015; Van Herpen et al 2006; Ozuna et al 2015). …”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Among these, 446 showed a full open reading frame (full ORF). The 18 remaining sequences (3.9 %) had at least one premature stop codon (PSC) and were designated as pseudogenes, in line with previous publications (Noma et al 2015; Van Herpen et al 2006; Ozuna et al 2015). …”
Section: Resultssupporting
confidence: 75%
“…Working on genomic DNA, Anderson and Greene (1997) showed that about half of the α-gliadin genes from bread wheat displayed at least one PSC. More recently, Ozuna et al (2015) found pseudogene proportions of 39, 76 and 63 % in the genomes of diploid, tetraploid and hexaploid wheat species, respectively. Polyploidization might have contributed to this increase in PSC occurrence because the genetic redundancy created by polyploidy can change the dynamics of coding sequence evolution and lead to the accumulation of PSC in duplicated genes (Akhunov et al 2013; Mighell et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the differences in epitopes comprising 33-mer peptide, α-gliadins can be divided into six types. Only Type 1 encompasses proteins including 33-mer peptide (from hexaploid wheat), whereas other types do not [30]. …”
Section: Classification and Structure Of Gluten Proteinsmentioning
confidence: 99%
“…Using RNA-amplicon sequencing (NGS) technology it was shown that α-gliadins can be separated into six types and only one type contains all the immunogenic peptides and epitopes, whereas the other five types do not contain all the epitopes disabling 33-mer peptide formation [30]. Thus, distinct types of α-gliadins differ mainly in the number of repeat blocks consisting in interspersed motifs PFPPQQ and PYPQPQ.…”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%